COFFEE TOURISM DEVELOPMENT STRATEGY BASED ON LOCAL CULTURE AS AN EFFORT TO INCREASE INCOME DURING THE COVID 19 PANDEMIC IN ACEH CENTRAL REGENCY - Ilham Satria, Dy; Yusra, Muhammad; Hilmi, Hilmi (International Journal of Educational Review, Law And Social Sciences (IJERLAS), 2021)
There are so many potential of Gayo highlands tourism, Central Aceh Regency, both natural tourism and cultural tourism. Based on initial observations from data from the Department of Culture, Tourism, Youth and Sports of Central Aceh Regency in 2018 with a total of 38 natural and artificial tourist objects, besides that the Gayo community has customs, culture and traditions that can become one of the cultural tourism destinations, as well as the potential for coffee plantations. For this reason, a more systematic study of tourism development management is needed by combining elements of existing physical and non-physical potential in order to increase the level of community income through the potential arising from tourism activities. The purpose of this study is to further examine the strategy of developing coffee tourism, both in the form of physical elements and non-physical elements through existing local wisdom as an effort to increase income, especially during the Covid19 Pandemic Period in Central Aceh Regency. The research method is descriptive qualitative with a sample of 40 respondents from coffee entrepreneurs and coffee shops in several tourist attraction areas. The results showed that Central Aceh Regency has great potential for the development of a coffee tourism model based on local culture in order to increase people's income, especially people who are directly involved in tourism management and coffee farmers.